Recycling intention and behavior among Low-Income Households - Al Mamun, Abdullah; Mohiuddin, Muhammad; Ahmad, Ghazali; Thurasamy, Ramayah; Fazal, Syed Ali (2018)
To improve our knowledge of how to protect the environment, this study examined the factors that influence recycling intention and behavior among low-income households. The study adopted a cross-sectional design that relied on 380 low-income households who live in coastal Peninsular Malaysia. The findings revealed a positive effect of eco-literacy, environmental concern, and self-efficacy on the attitude towards environmentally friendly products. Subsequently, the findings also illustrated a positive effect of normative beliefs on subjective norms. Moreover, the results revealed a positive effect of attitude towards environmentally friendly products and perceived behavioral control (PBC) on recycling intention. Finally, there was a positive effect of both PBC and recycling intention on recycling behavior. Although this study’s focus on a specific income group from a single country could limit generalizability; the findings nevertheless provide scholars and policymakers with significant insights into promoting recycling activities, which are expected to contribute to the environment and reduce the environmental and economic vulnerability among low-income households. Therefore, environmental and socio-economic development organizations should assess the feasibility of recycling materials and develop a supportive system that facilitates and encourages recycling activities.